(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The Republic of Croatia is geographically part of Eastern Europe. On this market, Croatia has accomplished the best results in export. The structure and the amount of foreign trade of the national economy depend on technological achievements, organizational superiority and managerial skills, and on that basis, lower costs, with an emphasis on high quality and differentiation of products and services. Following the aforementioned, in the modern economy, innovation often represents the key competence of a company. However, the complex nature of innovation is evident in the theoretical approach to innovation, contradictory results of studies and distinctive analyses of the impact of innovation on certain economic aspects. Therefore, the goal of this paper is to examine the innovations of goods and services in service of increasing the export in Eastern Europe on the sample of Croatian companies engaged in export activities. Results of the survey showed that innovation activities of companies, directed at the Eastern European market, have a negative impact on export activities in these markets. This result indicates actually that Croatian companies participate in foreign markets with already tested, wellestablished and well-known products. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.